Role of Shear Wave Elastography in Assessment of Placental Stiffness of Intrauterine Fetal Growth Restriction - W. Al Esawi , Riyadh; Alaa Abdul Ameer Mahdi , Fatin (Hammurabi Journal of Medical Sciences, 2025)
Background: Ultrasound play a crucial part in evaluating both normal and high-risk pregnancy . A new ultrasonographic method called shear wave elastography (SWE) is used to measure the elasticity of soft tissues and provide an accurate representation of their composition. Objectives: The purpose of this study is to assess placental stiffness in both growths restricted fetuses and normal fetal growth. Materials and Methods: A case-control study that involved 100 singleton pregnant women (fifty fetal growth-restricted pregnant women and fifty normal pregnancies as controls), was conducted at the Ultrasound Clinic at Al-Zahraa Teaching Hospital in Al-Najaf governorate, between December 2022 into December 2023. All pregnant women were in their 3rd trimester. All subjects were examined using the GE LOGIC E9 XD Clear ultrasound system with a convex probe (C1-6 probe) and underwent B-mode ultrasonography, Doppler study, and placental 2D SWE examinations. Results: Doppler ultrasound results showed mean S/D (2.30 ± 0.35), RI (0.55 ± 0.08), and PI (0.72 ± 0.05) in normal pregnancies, while S/D (5.34 ± 2.58), RI (0.80 ± 0.09), and PI (1.69 ± 0.46) were found in all fetuses in the growth-restricted group.There was a significant difference in the mean placental SWE values between studied groups, where the highest means were found among pregnant with growth restricted pregnancy (11.25 ± 2.69 KPa) while lowest mean was found among normal pregnant (3.13± 0.24 KPa), sensitivity and specificity were 100% and 100% respectively ,with cut-off value of (5.2 Kpa) that can differentiate between normal and abnormal placentae. Among fetal growth restricted mothers, (N=29) were hypertensive, (N=11) were diabetic, (N=8) hypertensive/ diabetic and , (N=10) non hypertensive non diabetic ,in which placental mean SWE measure (13±2.25 Kpa ), (10±2.43 Kpa), (13±2.53 Kpa) and (9±2.75 Kpa) respectively that is of non-significant correlation (P value 0.056). Conclusion: Placental stiffness was significantly higher in growth-restricted pregnancy mainly those who have hypertension and diabetes) than in normal pregnancy. There is a strong correlation between placental stiffness & Amniotic fluid index in addition to placental thickness. No correlation between placental stiffness & Doppler US indices (S, RI & PI).